Interactive Digital Module Development For Mathematical Representation Skills Using A Contextual Learning Approach - Nugroho Noto Priatmajo; Fertilia Ikashaum (Indonesian Mathematics Education Journal, 2025)
The need for technology-based teaching materials that align with online learning environments has significantly increased in the past two years. This shift has led to the transition from traditional teaching resources to digital learning materials. This study aims to develop an interactive digital module focused on statistical material by contextualizing students' representational skills. The development process followed a design research methodology with a development study approach, which included preliminary and formative evaluations—namely self-evaluation, prototyping, and field testing. The participants of this study were eighth-grade students from Middle School 3 Metro. Data were collected using observation sheets, interviews, and student assessments. The results indicated that the interactive digital module met the "very feasible" category, as shown by material expert validation results of 85.71%, media expert validation of 90.6%, and teacher validation of 81.57%. Furthermore, the student’s average mathematical representation ability test score was 75.65. These findings suggest that the developed interactive digital module is appropriate for supporting the teaching and learning process in mathematics, particularly in statistics. The module can serve as an effective tool to enhance students' conceptual understanding through contextual and interactive digital content.